PENGARUH MODEL PROBLEM BASED LEARNING (PBL) VERSUS PROJECT BASED LEARNING (PjBL) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA - satuti, Luxmita Anna; Sabariah; Suharti (JS (JURNAL SEKOLAH), 2025)
Abstract: This study aims to analyze the effects of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models, as well as students’ learning motivation, on mathematics learning outcomes among fifth-grade elementary students. The research was motivated by persistently low mathematics achievement at the primary level, often attributed to teacher-centered approaches and insufficient student motivation. A 2x2 factorial experimental design was employed, involving 54 students from SD Negeri Inpres Malompo, Papua, divided into two experimental groups: Class A using the PBL model and Class B using the PjBL model. Data were collected through a mathematics achievement test and a learning motivation questionnaire, both validated for reliability and content. Data analysis was conducted using Two-Way ANOVA. The results revealed that the instructional model did not have a significant effect on mathematics learning outcomes (p = 0.107), while learning motivation had a highly significant effect (p = 0.000). Moreover, there was no significant interaction between the instructional model and motivation level (p = 0.435). These findings suggest that learning outcomes are more strongly influenced by individual motivation rather than the choice of instructional model. The coefficient of determination (R²) of 0.545 indicates that 54.5% of the variance in learning outcomes can be explained by the combined effects of the instructional model and learning motivation.This study highlights the importance of strengthening students’ learning motivation as a central focus in improving mathematics instruction in elementary schools, alongside the contextual and adaptive use of innovative teaching models.  Keyword: Problem-Based Learning, Project-Based Learning, learning motivation, mathematics achievement, elementary education.   Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Problem-Based Learning (PBL) dan Project-Based Learning (PjBL) serta tingkat motivasi belajar terhadap hasil belajar matematika siswa kelas V sekolah dasar. Latar belakang penelitian ini berpijak pada rendahnya hasil belajar matematika di tingkat dasar yang sering kali dipengaruhi oleh penggunaan metode pembelajaran konvensional dan lemahnya motivasi belajar siswa. Penelitian ini menggunakan rancangan eksperimen faktorial 2x2 dengan subjek sebanyak 54 siswa di SD Negeri Inpres Malompo, Papua, yang terbagi dalam dua kelas eksperimen: kelas A menggunakan model PBL dan kelas B menggunakan model PjBL. Data dikumpulkan melalui tes hasil belajar dan angket motivasi belajar, yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan menggunakan Two-Way ANOVA. Hasil penelitian menunjukkan bahwa model pembelajaran tidak berpengaruh signifikan terhadap hasil belajar matematika (p = 0,107), sedangkan motivasi belajar memberikan pengaruh yang sangat signifikan (p = 0,000). Tidak ditemukan interaksi yang signifikan antara model pembelajaran dan tingkat motivasi terhadap hasil belajar (p = 0,435). Temuan ini menunjukkan bahwa keberhasilan belajar lebih ditentukan oleh tingkat motivasi siswa dibandingkan dengan model pembelajaran yang digunakan. Koefisien determinasi (R²) sebesar 0,545 mengindikasikan bahwa 54,5% variasi hasil belajar dapat dijelaskan oleh kombinasi model pembelajaran dan motivasi belajar. Penelitian ini merekomendasikan pentingnya penguatan motivasi belajar siswa sebagai fokus utama dalam pengembangan strategi pembelajaran matematika di sekolah dasar, serta penerapan model inovatif yang kontekstual dan adaptif terhadap karakteristik peserta didik. Kata Kunci: Problem-Based Learning, Project-Based Learning, motivasi belajar, hasil belajar matematika, sekolah dasar.